Reconciliation of Conflicting Societal Objectives: Nature Protection vs. Mining - Eberhard Falck; Vitor Correia (Materials Proceedings, 2023)
Critical raw materials (CRMs) like lithium, cobalt, and copper are crucial for our modern economy, driving digitalisation and the energy transition. The EU-funded CIRAN project addresses the challenge of balancing environmental protection and the demand for CRMs. It focuses on developing innovative land-use governance models, social contract frameworks, and business models. These initiatives enable informed and sustainable decisions in mining operations, fostering environmental protection while meeting the growing need for CRMs.